Educomunicación televisiva para la sensibilización de la comunidad transgénero por medio de la Organización Transfeminista Cuerpos Distintos, norte de Quito, año 2025 - Sánchez Aragón, Emilia Alexandra (2025)
This paper examines television educommunication as a strategic resource for raising awareness and visibility of the transgender community in Quito, taking as a reference the work of the transfeminist organization “Cuerpos Distintos” (Different Bodies). The study adopts a mixed approach that combines surveys of 316 residents of the Iñaquito parish, interviews with activists, and focus groups with the Transmasculine Fraternity. These methods allowed for the analysis of social perceptions, levels of awareness, and the importance of audiovisual content in the construction of inclusive narratives. The research shows that, although there is growing recognition of sex and gender diversity, information gaps, stereotypes, and limited representations still prevail in traditional media. The results show that audiovisual formats such as documentaries, testimonials, and community productions are valued by the population as effective tools for fostering empathy, respect, and social recognition. It is also concluded that television educommunication has the potential to contribute to cultural transformation by promoting critical and participatory discourses on gender identity. Within this framework, the production of the documentary “Mi nombre, mi historia” (My Name, My Story) is proposed, which compiles life testimonies of transgender people as an educommunication proposal aimed at raising public awareness and increasing the visibility of the community.